The Philippines : Country Environmental Analysis - World Bank (World Bank, 2012)
The objectives of this Country Environmental Analysis (CEA) were to assess the environmental quality in the Philippines with a focus on how this affects human welfare and sustainability, measure and analyze the biophysical significance and monetary cost of environmental degradation and derive priority areas of action, assess the Philippines government's capacity to manage the environmental challenges identified, and identify opportunities for reform and interventions. The Philippines has sound and comprehensive environmental laws and policies. However, it suffers from weak implementation because of inadequate capacity and financial constraints both at the national and local levels. A shift in strategy toward more devolution to local levels of government, enhanced resource mobilization for environmental management, better prioritization, and retooling of human resources are urgently needed to accommodate new priorities. The CEA also recommends improvements in environmental information systems and public access to such information.